Модифікована рослинна олія як основний компонент змащувально-охолоджуючої рідини - Балицький, Олександр; Гаврилюк, Марія; Дев'яткін, Роман (КІНПАТРІ ЛТД, 2013)
As a result of the thermo-mechanical degradation of components of the LCL are active radicals fatty acids created and atomic hydrogen arised. Active radicals has interact with juvenile surface of the specimen and the tool, reducing energy consumption in the process of cutting.
The modification modified vegetable oil as the main component lubricating-cooling liquids